EMAMECTIN BENZOATE EXPOSURE IMPAIRED GERM CELL MATURATION IN THE TESTES OF ADULT ALBINO RATS - Kamel, Assia; Akdader-Oudahmane, Samira; Hamouli-Said, Zohra (Polish Journal of Natural Sciences, 2024)
Certain pesticides represent a substantial risk to reproductive function, and their possible reprotoxic effects have been the focus of numerous research. Emamectin Benzoate (EMB), a biopesticide widely used in agriculture, household items, and veterinary health, can cause tissue damage in the male reproductive system due to oxidative toxicity. The purpose of this study was to investigate the effects of Emamectin Benzoate toxicity in male Wistar rats. Fourteen rats were divided into two groups of seven each. For 15 days, the EMB group received a daily dose of EMB corresponding to 20 mg/Kg by gavage. Distilled water was given to the control group. Oxidative stress, DNA fragmentation, histopathology and germ cell degeneration of testis were investigated. Emamectin administration induced oxidative stress in testicle evidenced by elevated levels of MDA, protein carbonyl and percentage of DNA fragmentation with depletion of the defense system (CAT and SOD activities). Emamectin produced several histopathological changes in the testis, these results suggest that the subchronic exposure to emamectine benzoate affects the redox state which contribute to testicular impairment.